Acquisition of english wh-questions by Kadazandusun speakers in Malaysia - Muin, Jessy (2016)
A number of studies have looked into the acquisition of English wh-questions by different first language (L1) groups. However, there is yet a study on the acquisition of English wh-questions by L1 Kadazandusun speakers of second language L2 English. This study, therefore, attempts to address this lack. It will test the claims and predictions of two competing hypotheses: the Full Transfer Full Access Hypothesis (FTFA) (Schwartz and Sprouse, 1994, 1996) and the Representational Deficit Hypothesis (RDH) (Hawkins, 2005). The FTFA hypothesis proposes that post-childhood L2 learners start out with L1 parameterised features present in the syntactic functional categories and, subsequently, they are able to reset the L1 parameters to the L2 setting. RDH proposes that post-childhood L2 learners experience syntactic deficit in L2 if syntactic functional categories present in the L2 are not instantiated in the L1. Wh-questions in both English and Kadazandusun are formed via wh-movement. However, while English obeys movement constraints such as the Subjacency Condition (Wh-island Constraint, Sentential Subject Constraint and Complex Determiner Phrase Constraint) and Empty Category Principle (ECP) (Comp-trace effect), Kadazandusun does not seem to be sensitive to these constraints. A hundred and six (106) L1 Kadazandusun speakers of L2 English from three proficiency groups participated in the study. Three instruments, the Oxford Placement Test (OPT) (Allan, 2004), a Grammaticality Judgement Test (GJT) and Question Formation Test (QFT) (adapted from Wong, 1999) were administered to the participants. The OPT was used to group the participants into three proficiency groups while the GJT and QFT were used to test the participants’ surface and underlying knowledge of English wh-questions. To test for significant differences of the results obtained from the three groups of participants, the nonparametric Kruskal-Wallis test, followed by pairwise comparisons, was used to analyse the data. A nonparametric test rather than a parametric test was chosen to analyse the data because the participants were not randomly selected but they were selected by using the snowball sampling method. The findings showed that there seemed to be wh-movement in the L1 Kadazandusuns’ interlanguage grammars. However, their underlying representations were far from native-like as they were not able to reject ungrammatical stimuli with Subjacency and ECP constraints. The findings of the study thus seemed to support the RDH (Hawkins, 2005). Such findings are further contribution to the field of second language acquisition (SLA) literature, in particular to the partial access to Universal Grammar (UG) view in the acquisition of L2. In addition, the findings would have pedagogical implications for the English as a second language (ESL) classroom, in particular in the East Malaysian state of Sabah.